Neoliberalismo y educación - Padilla Caíña, Euclides (2014)
The aim of this article is to analyze Neoliberalism as an ideology that is part of globalization and its relationship with present educaction –the new neoliberal school-, in which the student –homo sapiens- become a “homo videns”, as a result of the licentiousness caused by Neoliberalism.